Using Transcriptomics to Identify Differential Gene Expression in Response to Salinity among Australian Phragmites australis Clones - Holmes, Gareth D.; Hall, Nathan E.; Gendall, Anthony R.; Boon, Paul I.; James, Elizabeth A. (Frontiers in Plant Science, 2016)
Common Reed (Phragmites australis) is a frequent component of inland, and coastal, wetlands in temperate zones worldwide. Ongoing environmental changes have resulted in the decline of this species in many areas and invasive expansion in others. In the Gippsland Lakes coastal waterway system in south-eastern Australia, increasing salinity is thought to have contributed to the loss of fringing P. australis reed beds leading to increased shoreline erosion. A major goal of restoration in this waterway is to address the effect of salinity by planting a genetically-diverse range of salt-tolerant P. australis lineages. This has prompted an interest in examining the variation in salinity tolerance among lineages and the underlying basis of this variation. Transcriptomics is an approach for identifying variation in genes and their expression levels associated with the exposure of plants to environmental stressors. In this paper we present initial results of the first comparative culm transcriptome analysis of P. australis clones. After sampling plants from sites of varied surface water salinity across the Gippsland Lakes, replicates from three clones from highly saline sites (>18 g L-1 TDS) and three from low salinity sites (<6 g L-1) were grown in containers irrigated with either fresh (<0.1 g L-1) or saline water (16 g L-1). An RNA-Seq protocol was used to generate sequence data from culm tissues from the 12 samples allowing an analysis of differential gene expression. Among the key findings, we identified several genes uniquely up- or down-regulated in clones from highly saline sites when irrigated with saline water relative to clones from low salinity sites. These included the relative higher expression levels of genes associated with photosynthesis and lignan biosynthesis indicative of a greater ability of these clones to maintain growth under saline conditions. Combined with growth data from a parallel study, our data suggests local adaptation of certain clones to salinity and provides a basis for more detailed studies.